`lim_(x->oo) (x - ln(x))` Find the limit. Use l’Hospital’s Rule where appropriate. If there is a more elementary method, consider using it. If l’Hospital’s Rule doesn’t apply,...

`lim_(x->oo) (x - ln(x))` Find the limit. Use l’Hospital’s Rule where appropriate. If there is a more elementary method, consider using it. If l’Hospital’s Rule doesn’t apply, explain why.

Asked on by enotes

1 Answer

gsarora17's profile pic

gsarora17 | (Level 2) Associate Educator

Posted on

`lim_(x->oo)x-ln(x)`

`=lim_(x->oo)x(1-ln(x)/x)`

`=lim_(x->oo)x(1-lim_(x->oo)ln(x)/x)`

Now let us evaluate

`lim_(x->oo)ln(x)/x`

Apply L'Hospital rule , Test condition:

`lim_(x->oo)((ln(x))')/(x')=1/x=1/oo=0`

`=lim_(x->oo)x(1-0)`

plug in the value,

`=oo(1-0)=oo`